DSL for Collaborative Systems with Awareness - Bibbo, Luis (2017)
Domain Specific Languages (DSLs) are high-level languages defined for combining expressiveness and simplicity by means of linguistic constructs which are close to the problem domain but independent of the complexities inherent to the underlying software implementations. This article presents the CSSL v2.0 language that allows defining in precise, concise and friendly manner the abstract concepts of collaborative systems. Specially, the language makes available the concepts of awareness and collaborative processes. The language is independent of both the framework and the development tools and allows the application of the MDD approach to the development of such systems. The CSSL v2.0 language was designed as a UML extension using the metamodeling mechanism and was implemented with open source tools on the Eclipse platform. It provides improvements on previous proposals by enabling more complete and complex specifications of collaborative situations.